2010
DOI: 10.1111/j.1440-1835.2009.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Gambierdiscus spp. (Gonyaulacales, Dinophyceae) in Japanese coastal areas

Abstract: The genetic diversity of the ciguatera fish poisoningrelated dinoflagellate distributed in Japanese coastal areas was investigated. The entire sequence of the 5.8S rRNA gene and two internal transcribed (ITS) regions were determined, which included putative pseudogenes, from 19 strains of dinoflagellates assigned to the genus Gambierdiscus Adachi et Fukuyo collected from Japanese subtropical and temperate coastal areas. The sequences obtained from the 19 strains were divided into two types based on sequence si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
(48 reference statements)
2
24
0
Order By: Relevance
“…Type 2, in the SSU rDNA tree (Fig. 1), was solely comprised of Japanese strains including 14 strains established in the present study (blue letters) and two strains (black letters) by Kuno et al [22].…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Type 2, in the SSU rDNA tree (Fig. 1), was solely comprised of Japanese strains including 14 strains established in the present study (blue letters) and two strains (black letters) by Kuno et al [22].…”
Section: Resultsmentioning
confidence: 63%
“…type 1 from the subtropical and Gambierdiscus sp. type 2 from the temperate areas [22]. Recently in 2011, Fraga et al [15] described G. excentricus by morphological and phylogenic analyses of the LSU rDNA D1–D3 and the LSU rDNA D8–D10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two genetically distinct Gambierdiscus populations, possibly with different origins, have been isolated indicating that multiple species might be present (Kuno et al, 2010). Gambierdiscus has also been reported in the Philippines (Gillespie, 1987), Hong Kong (Lu and Hodgkiss, 2004), and Vietnam , although the species diversity at these locales remains unknown at this time.…”
Section: Western Pacific and Southeast Asiamentioning
confidence: 94%
“…Litaker et al (2009) did present distinguishing morphological features, however, thereby providing concordance between morphologic and genetic differences. Kuno et al (2010) isolated 19 new strains of Gambierdiscus from the coastal waters of Japan and found that the strains fell into two geographic groups (Type 1-subtropical; Type 2-temperate) based on 5.8S rRNA sequences and ITS2 base pair length. Litaker et al (2010) conducted a global survey of Gambierdiscus using a phylogenetic analysis based on the results of Litaker et al (2009), also demonstrating a wide geographic range for some species, but not for others (discussed in more detail in the Geography section of this review).…”
Section: The Genus Gambierdiscusmentioning
confidence: 99%